Conservation of an isolated and genetically unique population: red squirrels on the Isle of Wight - Alyson E.V. Buchanan; Demetra Andreou; Kathy H. Hodder; Melissa A. Toups; Phillipa K. Gillingham; Marin Cvitanović; Helen Butler; Emilie A. Hardouin (Biodiversity and Conservation, 2025)
Island populations face a higher extinction risk than mainland ones due to their smaller population sizes, limited genetic diversity, and increased vulnerability to environmental changes and stochastic events. The Isle of Wight red squirrel population is culturally and economically significant, being the largest remaining population in Southern England and genetically distinct from European populations. We used a multidisciplinary approach to assess the population’s long-term viability, evaluating habitat and food resources, analysing microsatellite genetic data, and using life history data to model population viability. Results indicated that natural food resources, supplemented by additional feeding, could sustain and support population growth. Microsatellite data identified two genetic clusters in the east and west of the island. Although F ST values were non-significant, indicating gene flow between subpopulations, elevated F IS values suggest localised mating dynamics driven by limited dispersal and spatial structure rather than systemic inbreeding. Population viability analyses suggested that habitat fragmentation and localised inbreeding do not pose immediate threats. However, maintaining connectivity between subpopulations remains crucial to preserving genetic diversity and reducing future risks of genetic isolation or increased inbreeding. Under pessimistic scenarios with reduced survival rates and fewer litters, model predictions indicated population decline and increased extinction risks. Future research should incorporate fine-scale spatial genetic analyses using genome data to explore population structure, local adaptation, and differentiate local mating dynamics from population-wide inbreeding. While direct data on inbreeding, litter sizes, and survival rates are challenging to obtain, these insights are critical for understanding population dynamics and guiding conservation efforts.